THE INFLUENCE OF DIRECT MARKETING AND ADVERTISING TOWARD CUSTOMER PURCHASE INTENTION IN APPLYING CONSUMER LOAN FOR GOVERNMENT EMPLOYEES AT PT.BANK SULUT AMURANG BRANCH - Rawung, Nadia (JURNAL BERKALA ILMIAH EFISIENSI, 2015)
ABSTRACT An era that had been developed at this time, competition make the business required to be able to carry out strategies to retain their business. Companies must deliver products and services by using promotion mix, company had to understand the behavior of consumers in order to maintain customer. The main objective of this study is to understand the influence of direct marketing and advertising toward customer purchase intention in applying consumer loan for government employees at PT.Bank Sulut Amurang Branch. 50 customers of PT.Bank Sulut Amurang were surveyed as respondents. The result indicated that Advertising have a significant influence on customer purchase intention and direct marketing does not have a significant influence on customer purchase intention. This study suggests for government employees that want to develop their business but have not enough money, so they can take consumer loan for government employees that PT.Bank Sulut provide. Keyword: Direct Marketing, Advertising, Customer Purchase Intention